Higher education in Scotland and the UK : diverging or converging systems? - Riddell, Sheila, 1953-; Weedon, Elisabet; Minty, Sarah (Edinburgh University Press, 2016)
Exploring the impact on Scottish higher education of major constitutional change in Scotland and the UK. This book focuses on the challenges and opportunities faced by Scottish higher education post-referendum 2014. It draws on findings from a project on higher education within the ESRC's Future of the UK and Scotland Programme, making an important and original contribution to the understanding of higher education policy in Scotland and the rest of the UK. Central themes explored in different chapters include: the influence of marketisation and internationalisation on Scottish and UK higher education systems; university governance, devolution and the rescaling of the European state; the impact of widening access policies on territorial and social justice; young people's views of higher education and the impact of the extended franchise; cross-border student flows and migration; research funding, knowledge economies and constitutional change. Key features First book to explore the impact on Scottish higher education of major constitutional change in Scotland and the UK Analyses the impact of marketisation and internationalisation on Scottish and UK higher education in the light of new constitutional arrangements Explores the implications of different fees and student support regimes for cross-border student flows and territorial and social justice Considers the extent to which widening access policies in Scotland and the UK have opened up higher education for under-represented groups and the future of such policies in a new Scotland Looks at the possible impact of a new immigration regime on the recruitment of international students, and the implications of different immigration rules for a common UK travel area Examines the way in which higher education is viewed by young people in Scotland and England.